2018
DOI: 10.1038/s41467-018-07697-7
|View full text |Cite
|
Sign up to set email alerts
|

Near-zero effective impedance with finite phase velocity for sensing and actuation enhancement by resonator pairing

Abstract: In spite of the extensive studies of zero-index metamaterials, the realization of zero impedance with finite phase velocity has not been explored. Here, we show that this extreme case, realized by elaborately-tuned paired resonators, can effectively enhance sensing and actuation. To explain the formation mechanism of the near-zero effective impedance with finite phase velocity by paired resonators at a target frequency, a theory using an equivalent model based on mechanical longitudinal waves is developed. If … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…In contrast to fluid-like pentamode metamaterials, Zheng et al [130] proposed singly polarized elastic metamaterials whose shear modulus is much greater than their bulk modulus, as shown in figure 8(b); the resulting metamaterials mainly support the propagation of shear waves. It is worth mentioning that there are investigations on near-zero effective rotational stiffness [131] and near-zero effective impedance [132] using elastic metamaterials.…”
Section: Near-zero and Near-infinity Materials Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to fluid-like pentamode metamaterials, Zheng et al [130] proposed singly polarized elastic metamaterials whose shear modulus is much greater than their bulk modulus, as shown in figure 8(b); the resulting metamaterials mainly support the propagation of shear waves. It is worth mentioning that there are investigations on near-zero effective rotational stiffness [131] and near-zero effective impedance [132] using elastic metamaterials.…”
Section: Near-zero and Near-infinity Materials Propertiesmentioning
confidence: 99%
“…The PZT is supposed to generate longitudinal waves (corresponding to the S0 mode) in a plate. Kim et al [132] showed that elaborately designed U-shaped structures functioning as resonators can make the effective impedance of the excitation region surrounded by the structures near zero at a selected excitation frequency. Furthermore, if the excitation frequency can be tuned at a Fabry-Pérot resonance frequency, the far-field output by the transducer can be dramatically increased.…”
Section: Actuation and Sensingmentioning
confidence: 99%
“…It has been reported [27] that the distributed excitation of the plate by the patch can be accurately modeled by the two concentrated pin forces if the farfield wave motion is of interest. Using this method, many studies [6,14,25] have described the wave generating mechanism of MPTs. The comparison of the frequency characteristics of a wave output by the detailed model and the pin-force based model supports the validity of the used pinforce assumption over the frequency range of interest.…”
Section: Theoretical Analysismentioning
confidence: 99%
“…The idea to introduce an additional resonator is inspired by the fact that a dynamic absorber based on a mechanical resonator absorbs vibration energy at a tuned frequency [20][21][22][23], but it can also amplify the vibration near the tuned frequency [24,25]. A recent study [24,25] has further shown that if elaborately tuned resonators are employed, near-zero effective impedance with a finite phase velocity can be realized, possibly resulting in high enhancement of the sensing and actuation of a piezoelectric transducer. Along this line, we are proposing a nonstereotypical approach involving the use of an energyabsorbing resonator as a power-boosting resonator operating at a detuned frequency.…”
Section: Introductionmentioning
confidence: 99%